Small-molecule compound SYG-180-2-2 attenuates Staphylococcus aureus virulence by inhibiting hemolysin and staphyloxanthin production - Rao, Lulin; Xu, Yanlei; Shen, Li; Wang, Xinyi; Zhao, Huilin; Wang, Bingjie; Zhang, Jiao; Xiao, Yanghua; Guo, Yinjuan; Sheng, Yaoguang; Cheng, Lixia; Song, Zengqiang; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
Multi-drug resistant Staphylococcus aureus infection is still a serious threat to global health. Therefore, there is an urgent need to develop new antibacterial agents based on virulence factor therapy to overcome drug resistance. Here, we synthesized a small molecule compound SYG-180-2-2 (C21H16N2OSe) with anti-virulence ability. The aim of this study was to investigate the anti-virulence efficacy of SYG-180-2-2 against Staphylococcus aureus. The growth curve assay showed that SYG-180-2-2 had nonlethal effect on S. aureus. Besides, SYG-180-2-2 strongly inhibited the hemolytic activity and staphyloxanthin synthesis in S. aureus. Inhibition of staphyloxanthin by SYG-180-2-2 enhanced the sensitivity of S. aureus to oxidants and human whole blood. In addition, SYG-180-2-2 significantly decreased the expression of saeR-mediated hemolytic gene hlb and staphyloxanthin-related crtM, crtN and sigB genes by quantitative polymerase chain reaction (qPCR). Meanwhile, the expression of oxidative stress-related genes sodA and sodM also decreased. Further, Galleria Mellonella assay revealed that SYG-180-2-2 was not toxic to larvae and the survival rate of larvae greatly improved at the concentration of 4 μg/mL. SYG-180-2-2 also reduced skin abscess formation in mice by reducing bacterial burden and subcutaneous inflammation. In conclusion, SYG-180-2-2 might be a promising agent to attenuate the virulence of S. aureus by targeting genes associated with hemolytic activity and staphyloxanthin synthesis.